Construction and performance evaluation of a CSC-1 type horizontal rotating micro-bomb combustion-solution isoperibol multifunctional calorimeter. (September 2021) - Li, Xu; Li, Qiang-Guo; Li, Chuan-Hua; Duan, Ling-Fei; Jiang, Jian-Hong; Zeng, Fan-Hua; Li, Xia; Gu, Hui-Wen
Graphical abstract: Highlights: A new combustion-solution isoperibol multifunctional calorimeter was constructed. Dewar bottle was used as a calorimetric vessel for determination of combustion heat. The submersible magnetic mixer replaced conventional mechanical rod mixer. A rotating system composed of collector rings of 24 gold contact points was designed. The micro-bomb in the combustion system can 360° rotate horizontally. Abstract: In this work, a CSC-1 type horizontal rotating micro-bomb combustion-solution isoperibol multifunctional calorimeter was constructed. There are three main differences between the structure of this calorimeter and the existing calorimeters: (1) two functions, i.e. the measurements of combustion heat and solution heat were integrated together; (2) Dewar bottle was used as a shared calorimetric container for the determination of combustion heat and solution heat; (3) submersible magnetic mixer replaced the traditional mechanical rod mixer. The energy equivalent of combustion system in the calorimeter was calibrated with NIST SRM 39j benzoic acid, giving the result of (1181.94 ± 0.23) J⋅K −1 . Furthermore, the standard specific energy of combustion of salicylic acid was measured using the combustion system, and the result showed that the standard specific energy of combustion of salicylic acid was – (21884.9 ± 5.4) J·g −1 at 298.15 K. Then, the standard molar enthalpy of formation of salicylic acid was calculated to be Δ f H m o [ C 7 H 6 O 3 (s), 298.15 K ] = - ( 589.27 ± 2.98 ) kJ⋅mol −1 . In addition, the energy equivalent of solution system in the calorimeter was calibrated with electrical energy, giving the result of (5.28084 ± 0.00261) J·mV −1 . And the standard specific enthalpy of solution of KCl was measured by the solution system in water at 298.15 K, the results indicated that the standard specific and molar enthalpy of solution of KCl (1100 H2 O, 298.15 K) were (235.33 ± 0.03) J·g −l and (17543.2 ± 8.9) J·mol −l, respectively. All these results demonstrated that the calorimetric systems of combustion and solution in the developed calorimeter are reliable and feasible.